Initiation and termination of duck hepatitis B virus DNA synthesis during virus maturation. - Lien, J M (1987)
We characterized a number of important features of the structure of the cohesive overlap region of the DNA genome of duck hepatitis B virus. The 5'-terminal nucleotide of minus-strand DNA was localized to nucleotide 2537, a G residue within the 12-base repeat sequence DR1. This G residue was shown to be the site of a covalent linkage to a protein, consistent with speculation that this protein is the primer of minus-strand synthesis, which occurs by reverse transcription. The 3' terminus of the minus strand was heterogeneous, being mapped to nucleotides 2530 and 2531, indicating that the minus strand is terminally redundant by seven or eight bases and ends at the putative 5' end of the transcribed RNA template (pregenome) for reverse transcription. We previously demonstrated that the presumptive RNA primer of plus-strand synthesis remains attached to plus-strand DNA during virus maturation; moreover, the sequence of this primer suggested an origin from the 5' end of the pregenome (J.-M. Lien, C. E. Aldrich, and W. S. Mason, J. Virol. 57:229-236, 1986). We show here that over 75% of plus-strand primers are capped, further supporting the idea that these primers are uniquely derived from the 5' end of the pregenome. Finally, we found that seemingly mature duck hepatitis B virus genomes are incomplete by at least 12 bases, in that the 12-base repeat sequence DR2 is not copied into plus-strand DNA during virus maturation. Since DR2 in virion DNA is duplexed with the RNA primer of plus-strand synthesis, it is possible that the failure to make complete plus strands is due to an inability of the viral DNA polymerase to carry out a displacement of the bound RNA primer.